High‐Performance, Flexible NO2 Chemiresistors Achieved by Design of Imine‐Incorporated n‐Type Conjugated Polymers. Issue 14 (20th March 2022) - Park, Hyeonjung; Kim, Dong‐Ha; Ma, Boo Soo; Shin, Euichul; Kim, Youngkwon; Kim, Taek‐Soo; Kim, Felix Sunjoo; Kim, Il‐Doo; Kim, Bumjoon J.
Abstract: Flexible and mechanically robust gas sensors are the key technologies for wearable and implantable electronics. Herein, the authors demonstrate the high‐performance, flexible nitrogen dioxide (NO2 ) chemiresistors using a series of n‐type conjugated polymers (CPs: PNDIT2/IM‐ x ) and a polymer dopant (poly(ethyleneimine), PEI). Imine double bonds (C = N) are incorporated into the backbones of the CPs with different imine contents ( x ) to facilitate strong and selective interactions with NO2 . The PEI provides doping stability, enhanced electrical conductivity, and flexibility. As a result, the NO2 sensors with PNDIT2/IM‐0.1 and PEI (1:1 by weight ratio) exhibit outstanding sensing performances, such as excellent sensitivity (Δ R / R b = 240% @ 1 ppm), ultralow detection limit (0.1 ppm), high selectivity (Δ R / R b < 8% @ 1 ppm of interfering analytes), and high stability, thereby outperforming other state‐of‐the‐art CP‐based chemiresistors. Furthermore, the thin film of PNDIT2/IM‐0.1 and PEI blend is stretchable and mechanically robust, providing excellent flexibility to the NO2 sensors. Our study contributes to the rational design of high‐performance flexible gas sensors. Abstract : In this study, a high‐performance flexible NO2 chemiresistor (IM‐ x /P‐ y ) is developed based on n‐type conjugated polymers containing imine bonds in the backbone. Excellent overall sensing performances with ultralow limit of detection (LOD) are demonstrated.